Unifying effective psychotherapies : tracing the process of change - Fraser, J. Scott (American Psychological Association, 2018)
"The area of psychotherapy has adopted positivist paradigm and its medical model and clinical trials methods as it has perused answers to what works in psychotherapy. This book is about unifying effective approaches to psychotherapy--that is, finding the common process underlying all therapeutic change. It comprises three parts containing 12 chapters. Part I tracks the journey taken so far by researchers addressing what works in psychotherapy. It looks at progress made in research addressing evidence-supported psychotherapy. The book then looks closer at how to find the "truth" about what works, and describes alternative views on the nature of human interaction. It presents a long-standing alternate paradigm, termed a process view. The book suggests that this alternate paradigm, which incorporates the nature of change, the idea of process-based systems, and the influence of context, explains the common process underlying all effective psychotherapies. Part II examines the therapies that work for a range of different psychological and interpersonal problems to see whether the predictions of the process of change view hold up as a "golden thread" running through and connecting them all. It addresses evidence-supported treatments for anxiety, depression, posttraumatic stress disorder, and the interpersonal problems between couples and among family members. If the predictions of the process of change paradigm fit the data on all of these evidence-supported approaches across all of these problem areas, then a strong case will emerge for using it in the future to unify effective psychotherapies. Finally, Part III translates this process view into clinical practice."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)